Peculiarities Of Electrophysical Properties Of Arsenide Gallium Films Deposited Under Nonequilibrium Conditions - Kabyshev A. V. Alexander Vasilievich; Konusov F. V. Fedor Valerievich; Remnev G. E. Gennady Efimovich; Lozhnikov S. N.; Saltymakov M. S. Maksim Sergeevich (2010, 2010)
Title screen